Non-participation in breast cancer screening among previous cancer patients - Virgilsen, Line Flytkjær (J Cancer Res Clin Oncol, 2018)
PURPOSE: Breast cancer can be detected at early stages through organised screening. This study explored reasons for non-participation in breast cancer screening among previous cancer patients, who have high risk of developing a new primary cancer. METHOD: We conducted a population-based historical cohort study, including all women invited to the first organised screening round in 2008–2009 in the Central Denmark Region (n = 149,234). All data were based on national registers. RESULTS: Among women with previous cancer (n = 6638), 25.3% did not participate in breast cancer screening compared to 20.9% of women with no registrations of previous cancer, thus previous cancer patients were 21% less likely not to participate in breast cancer screening (PRR 1.21, 95% CI 1.16–1.27). Further analysis showed that this association was due to women receiving current cancer treatment or being in palliative care in the time leading up to screening. Women with previous malignant melanoma or colorectal cancer were more likely to participate in breast cancer screening, whereas women with previous gynaecological or “other” cancer types were less likely to participate. CONCLUSION: Screening for breast cancer may help diagnose breast cancer at an early stage. Women with previous cancer who are not undergoing current treatment or in palliative care have the same propensity to participate as other women invited to breast cancer screening. Women with previous gynaecological cancer were less likely to participate in breast cancer screening than women with other cancer types. These results may only be generalised to similar health care systems.